Improving the Efficiency of Acid-proof Finishing Cotton Fabrics by Using Cationic Polymers - Danchenko, Viktoriya; Saribekova, Diana (Видавництво Львівської політехніки, 2013)
The analysis of the possibility of using cationic preparation in the process of final finishing was made. Selection of technological mode of giving a cotton textile material acid-proof properties with the use of cationic polymers and potassium methylsiliconate were considered. It is shown that pre-treatment of textile material with a solution of a cationic preparation can significantly improve the durability of the protective effect for physico-chemical influence.
Keywords: acid-proof finishing; organosilicon compounds; cationic polymers; acid-resistance; cellulose containing material